Right and left ventricular interaction in pulmonary hypertension: Insight from velocity vector imaging. Issue 5 (15th April 2019) - Meng, Hong; Chandrasekaran, Krishnaswamy; Villarraga, Hector R.; Shah, Aijaz A.; Kittipovanonth, Maytinee; Cha, Stephen S.; Pellikka, Patricia A.; Seward, James B.
Abstract : Objective: To evaluate whether global peak systolic strain (PSS) and peak systolic strain rate (PSSR) derived from velocity vector imaging (VVI) allow early recognition of regional and global right ventricular (RV) dysfunction and the impact of this on left ventricular (LV) function in patients with pulmonary hypertension (PHT). Background: RV function is an important determinant of prognosis in patients with heart failure, pulmonary hypertension, heart transplant, and congenital heart diseases. However, evaluation of the right ventricle is often limited by its complex geometry and inadequate visualization of RV free wall. Furthermore, the impact of RV dysfunction on the LV function is not well elucidated. Methods: Ninety‐nine participants, 35 control patients with normal RV systolic pressure (RVSP) (<30 mm Hg) and 64 patients with PHT (25 with mild‐to‐moderate increase in RVSP [≥36 and <60 mm Hg] and 39 with severe increase in RVSP [≥60 mm Hg]), underwent comprehensive echo‐Doppler assessment and velocity vector imaging (VVI) for strain rate analysis. RV regional peak systolic and diastolic tangential velocity, strain, and strain rate were obtained from the basal, mid and apical segments of the RV free wall and interventricular septum (IVS) from apical 4‐chamber view at end‐expiration. Similar data were obtained from eighteen LV segments from apical 4‐chamber, 2‐chamber, and long‐axis views. Results: Peak systolic strain, strain rate, and tangential velocity at all segments in the RV free wall and IVS were decreased compared to controls in patients with PHT ( P  <   0.001). Significant correlation ( r  >   0.60; P  <   0.001) was noted between RVSP and systolic and diastolic strain and strain rate at basal segment in IVS and global RV function. Peak early diastolic strain rate at all segments was also decreased in PHT patients compared with control patients ( P  <   0.01). Furthermore, RV systolic and diastolic strain and strain rate were lower in group 2 with mild‐to‐moderate hypertension while the conventional echo parameters were normal. Except for IVS segments, other LV segments had no statistical differences in systolic and diastolic velocity, strain, and strain rate compared to controls. However, they were lower than the published normal range. Conclusions: Strain and strain rate derived from VVI demonstrates early recognition of systolic and diastolic RV dysfunction in patients with PHT compared to controls. PHT is associated with global and regional RV systolic and diastolic dysfunction. Systolic and diastolic strain and strain rate from LV was lower compared to controls but were not statistically significant. This may indicate subclinical LV dysfunction in these patients, suggesting that conventional LV function parameters may not be sensitive to recognize subclinical LV dysfunction. Mini‐Abstract: Right ventricular (RV) function is important in the prognosis of pulmonary hypertension (PHT). Novel strain and strain rate methods are used to assess RV function. However, data on RV function assessed by velocity vector imaging (VVI) in PHT are limited. Furthermore, the impact of RV dysfunction on LV function is not well known. We studied 35 controls and 64 PHT patients with normal LV function to determine whether PHT was associated with regional and global RV dysfunction using VVI. Compared with controls, systolic and diastolic strain and strain rate were decreased in PHT patients at all RV segments ( P  < 0.01); importantly, they were able to recognize RV dysfunction in group 2 with mild‐to‐moderate PHT where conventional echo parameters were normal. LV segments had no statistical differences in systolic and diastolic velocity, strain, and strain rate. However, lower values may indicate early subclinical LV dysfunction. Strain and strain rate derived from VVI can detect regional and global RV systolic and diastolic dysfunction early and subclinical LV dysfunction in PHT.